MENINGKATKAN KOMPETENSI GURU UNTUK MEWUJUDKAN PENDIDIKAN BERKUALITAS - Sustiana, Merlia; Abdurrahmansyah, Abdurrahmansyah; Amalia, Nur; Yolanda, Kenta (Jurnal Riset Madrasah Ibtidaiyah, 2025)
This study aims to determine how to improve teacher competence in order to realize quality education. This study uses a qualitative method with a library research approach that discusses Teacher Competence to Realize Quality Education. Literature or bibliography studies can be interpreted as a series of activities related to library data collection methods, reading and recording and processing research materials. This study employs a library research method by identifying, collecting, reviewing, and analyzing various scholarly sources such as books, journals, and educational policy documents to draw conclusions about strategies for improving teacher competencies in order to achieve quality education. The results of the study show that teacher qualifications and competency standards play an important role in improving the quality of education in Indonesia. Teachers must be able to adapt to technological advances, work with other teachers, and develop their professional skills. Pedagogical competence in education includes an understanding of the characteristics of their students. In addition, this understanding includes how teaching affects students, how to plan and implement learning activities, how to produce learning outcomes, and how to develop student potential. Personality competence is an important component of a teacher's competence.